A new amphibious species of the subterranean genus Bureschia Verhoeff, 1926 (Isopoda: Oniscidea: Trichoniscidae) from Serbia - Karaman, Ivo; Horvatović, Mladen (European Journal of Taxonomy, 2022)
Bureschia serbica sp. nov., is described from a cave in the Stara Planina Mt in Serbia as a second species in the genus. It is a troglobite amphibious species, predominantly aquatic like the nominal species of the genus, Bureschia bulgarica. The new species is adapted to amphibious life in running groundwater, unlike the nominal one that lives in subterranean lakes and ponds. Body structure changes, most noticeable the significant changes in the structure of the mouthparts, as a result of preadaptation in aquatic and amphibious Synocheta, are discussed.